Teacher Professionalism Certified Educators in the Implementation of Online Learning during the Covid-19 Pandemic - Mole, Paulina Nelce; Maria, Sonya Kristiani (Budapest International Research and Critics University, 2021)
This study aims to find out how professional teachers are in online learning during the covid-19 pandemic. The method used is a structured interview using a questionnaire in the form of a questionnaire and analyzed using a qualitative descriptive analysis. The subjects of this study were teachers who worked in senior high schools in Maumere and were certified educators. The research sample consisted of 10 people. From this research, it shows that the learning process has been implemented well but there are also obstacles in the learning process in the network. Where many students are unable to participate in learning activities due to the lack of good facilities by students when learning online which is caused because not all students have smartphones as online learning media, in addition, students are also found who cannot participate in learning because they are in areas with poor internet networks good.